2001
DOI: 10.1165/ajrcmb.25.6.4321
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-Mediated Apoptosis in Lung Epithelial Cells Is Regulated by Glutathione

Abstract: Reactive oxygen species (ROS) are mediators of lung injury, and glutathione (GSH) is the major nonprotein antioxidant that protects the cell from oxidative stress. We have recently shown that H(2)O(2) induces ceramide-mediated apoptosis in human lung epithelial cells. We hypothesized that ROS-mediated depletion of GSH plays a regulatory role in ceramide generation, and thus in the induction of apoptosis. Our present studies demonstrate that GSH at physiologic concentrations (1 to 10 mM) inhibits ceramide produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 34 publications
5
83
0
2
Order By: Relevance
“…A significant decrease in glutathione has also been measured. Lavrentiadou et al (2001) recently reported that the ROS-mediated depletion of glutathione plays a key role in ceramide generation by removing its inhibitory effect on neutral sphingomyelinase (Liu and Hannun, 1997;Liu et al, 1998). Therefore, we propose an amplification loop in which glutathione depletion is triggered by the induction of ROS and this drop in glutathione activates ceramide formation by the activation of neutral sphingomyelinase.…”
Section: Discussionmentioning
confidence: 73%
“…A significant decrease in glutathione has also been measured. Lavrentiadou et al (2001) recently reported that the ROS-mediated depletion of glutathione plays a key role in ceramide generation by removing its inhibitory effect on neutral sphingomyelinase (Liu and Hannun, 1997;Liu et al, 1998). Therefore, we propose an amplification loop in which glutathione depletion is triggered by the induction of ROS and this drop in glutathione activates ceramide formation by the activation of neutral sphingomyelinase.…”
Section: Discussionmentioning
confidence: 73%
“…Results were normalized to cells undergoing mock transfection and vehicle treatment (fetal bovine serum-free medium for CSE, or 0.1% ethanol for ceramide) for the same duration and compared with cells transfected with nontargeting siRNA. Both CSE and ceramide were previously reported to produce endothelial and alveolar septal cell apoptosis and airspace enlargement in rodent models (44,46) as well as endothelial and epithelial cell death in vitro (47)(48)(49)(50). Apoptosis was quantified using the Apopercentage kit (Biocolor Ltd., Accurate Chemical and Scientific Corporation, Westbury, NY) following the manufacturer's instructions.…”
Section: Assessment Of Apoptotic Cell Death In Vitromentioning
confidence: 99%
“…Cellular GSH levels are closely correlated with cell survival under adverse conditions (Bridges et al, 1991). Lavrentiadou et al (2001) demonstrated the role of GSH in preventing epithelial cell apoptosis. GSH depressed both early before ceramide production and it after events leading to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of N-SMase was higher in the SHRSP/IZM than in the WKY/IZM neurons. A previous report demonstrated that the expression of N-SMase via the initial production of ceramide was induced by the depletion of GSH (Lavrentiadou et al, 2001). Verheij et al, (1996) reported that ceramide induces the stress-activated protein kinase/c-jun kinase (SAPK/JNK) signaling that precedes apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation